Individual Counseling: Solutions for Traumatized Children of Sexual Violence - Pasya, Mhd. Fahrul Rozi; Wirtati, Ira (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study aims to explore the implementation of individual counseling by the government in dealing with trauma in child victims of sexual violence. This research uses a qualitative research type with a case study approach. The informants of this study were four people, one as a counselor and three others as a companion and monitor the development of victims of sexual violence. The data analysis technique used is Miles and Huberman's interactive thematic analysis, which includes the process of data reduction, data presentation, and conclusion drawing. The research findings show that the counseling stages carried out by the counselor begin with conducting an assessment, building rapport, then asking open questions, after that providing motivation, carrying out the diagnostic stage to diagnose problems in victims, and conducting prognosis to determine the treatment steps taken. The treatment of the findings of this study is to empower victims by conducting social training. The implication of this research is the importance of a comprehensive approach in handling trauma in victims of sexual violence, with a focus on empowerment and social rehabilitation.